AVNRT complicated by Valsalva-exacerbated radial pulsation artifacts mimicking acute ischemia: a case report - Li, Peng; Kan, Jingyu; Ding, Jingwen; Liu, Chongkai; Ding, Huaisheng (Frontiers in Cardiovascular Medicine, 2025)
Atrioventricular nodal reentrant tachycardia (AVNRT), the most common supraventricular tachycardia, occasionally present with transient ST-T changes mimicking ischemia, posing diagnostic challenges for patients. We report an 82-year-old woman with paroxysmal palpitations whose initial ECG demonstrated supraventricular tachycardia (154 bpm) accompanied by dynamic ST-segment elevation and T-wave inversion in leads I, II, aVL, and aVF, while lead III remained unaffected. Repositioning electrodes away from the right radial artery pulsation resolved these deviations, confirming their artifactual origin. The electrophysiological study confirmed the diagnosis of atrioventricular nodal reentrant tachycardia (AVNRT), and successful radiofrequency catheter ablation was performed with no recurrence during 6-month follow-up. Notably, breath-holding during tachycardia exacerbated pulsation artifacts by altering hemodynamic forces, a phenomenon further validated through provocative Valsalva maneuvers. This case highlights that limb pulsation artifacts—localized via Einthoven's triangle principles (sparing lead III)—can mimic ischemic patterns, particularly under tachycardia and breath-holding. Clinicians should prioritize ECG artifact exclusion through lead adjustment and dynamic testing to avoid unnecessary invasive interventions.